The use of information technologies in the educational space of Ukraine (on the example of steam technologies) - Knysh, Inna; Drobin, Andrii; Filimonova, Tetiana; Koycheva, Tetyana; Kushnir, Antonina; Kuchai, Oleksandr (Revista pedagógica de la Universidad de Cienfuegos, 2024)
In the process of experimental research, we proved the necessity of using information technologies in the educa-tional process of higher education institutions; the content of research concepts is revealed. A cloud-oriented system of using information technologies in the educational space of a higher school was built, the basis of which are speci-fic principles of using information technologies, professio-nally oriented information technologies in the educational space of a higher school, and the main methods of profes-sional training of future specialists, STEAM technologies, which made it possible to form future specialists relevant professional competences. In the process of research, the levels and elements of readiness of the future competitive specialist to use information technologies are distinguis-hed. The study allowed higher education students to use computer simulation programs to create educational com-plexes for self-education, which is the most effective form of using information technologies in education. During the study, effective specific principles of using information technologies were identified: the principle of distribution of educational and methodical material; the principle of interactivity in the organization of the educational space of the higher school; the principle of modularity of education; the principle of accessibility in the education system when presenting the content of education; the principle of ade-quate assessment of knowledge and feedback.
Keywords: information technologies; education; institutions of higher education; STEAM technologies; cloud-oriented system of using information technologies